Ecuador : Staff Report for the 2003 Article IV Consultation, Request for a Stand-By Arrangement, and Approval of an Exchange Restriction. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Ecuador's 2003 Article IV Consultation, a Request for a Stand-By Arrangement (SBA), and Approval of an Exchange Restriction. The main objectives of the fiscal program are to address immediate liquidity constraints and to bring expenditure growth under control, consistent with the demands of dollarization. The government has moved quickly to implement a package of politically difficult revenue measures. Although recognizing the risks involved, the IMF staff supports Ecuador's request for a new SBA in support of the government's economic program.